Job Creation, Job Destruction and Voting Behavior in Poland - Valérie Smeets; Frederic Warzynski (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
This paper analyzes the effect of job creation and job destruction on the voting patterns of individuals in Poland during the 1997 and 2001 parliamentary elections. First, we link the votes for the left wing party to the unemployment rate and the job creation and destruction rates in the constituency. We show that the job destruction rate and unemployment rate has a positive effect on the votes for the SLD, while the job creation rate has a negative effect. Second, we look at the effect of the change in job creation and job destruction rates on the change in the votes for individual candidates. We that incumbents from the firmer right wing coalition received less votes if excess job reallocation had increased in their constituency. Therefore, the paper provides evidence that job ?ows have a strong impact on voting patterns and that the balance between the positive and negative effects of refirms detfirmine to a large extent the political outcome.
Keywords: 330; Arbeitslosigkeit; Arbeitsmarkt; Beschäftigungseffekt; Wahlverhalten; Polen